2021
DOI: 10.1021/acs.est.0c08119
|View full text |Cite
|
Sign up to set email alerts
|

Consumption- and Income-Based Sectoral Emissions of Polycyclic Aromatic Hydrocarbons in China from 2002 to 2017

Abstract: China is the largest emitter of polycyclic aromatic hydrocarbons (PAHs) in the world. Because of their negative influences on human health, the characteristics and potential driving forces of PAH emissions should be evaluated to establish effective mitigation strategies for different economic sectors. This study is the first to quantify the embodied and enabled PAH emissions of 108 sectors in China in 2002, 2007, 2012, and 2017. The results show that the total sectoral emissions increased by 92% (from 28.0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…However, due to the differences in energy structures and policies, some countries like China may not have followed this emission trend (Figure 1 2017. Their results indicated that the total emissions increased from 2002 to 2012 (Li et al, 2021) which is consistent with the present study. While the emissions decreased from 2012 to 2017, and during this period inflection point of decoupling was not clear (Li et al, 2021).…”
Section: Dynamic Changes In Pahs Emissionssupporting
confidence: 93%
See 2 more Smart Citations
“…However, due to the differences in energy structures and policies, some countries like China may not have followed this emission trend (Figure 1 2017. Their results indicated that the total emissions increased from 2002 to 2012 (Li et al, 2021) which is consistent with the present study. While the emissions decreased from 2012 to 2017, and during this period inflection point of decoupling was not clear (Li et al, 2021).…”
Section: Dynamic Changes In Pahs Emissionssupporting
confidence: 93%
“…Their results indicated that the total emissions increased from 2002 to 2012 (Li et al, 2021) which is consistent with the present study. While the emissions decreased from 2012 to 2017, and during this period inflection point of decoupling was not clear (Li et al, 2021).…”
Section: Dynamic Changes In Pahs Emissionssupporting
confidence: 93%
See 1 more Smart Citation
“…Changes in production structure and efficiency gains caused the decline in CO 2 emissions embodied in exports 23 . Primary input and final demand structures had strong impacts on PAH emissions 24 . In addition, environmental factors mainly influence the atmospheric transportation of pollution, especially for PAHs, which tend to be particle-band.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous presence of PAHs in the atmosphere is dominated by the unavoidable byproducts of petrogenic and pyrogenic processes, which are strongly associated with various economic sectors. , Over the last few decades, globalization and international trade have connected worldwide economic sectors and have boosted global economic growth. However, international trade affects global air pollution and transport by redistributing emissions related to the production of goods and services and by potentially altering the total amount of global emissions.…”
Section: Introductionmentioning
confidence: 99%